2016
DOI: 10.1002/anie.201601899
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Catalyzed Stereoselective Cross‐Coupling Reactions of Stereodefined Enol Carbamates with Grignard Reagents

Abstract: A practical and highly stereoselective iron-catalyzed cross-coupling reaction of stereodefined enol carbamates and Grignard reagents to yield tri- and tetrasubstituted acrylates is reported. A facile method for the stereoselective generation of these enol carbamates has also been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 51 publications
(17 reference statements)
0
22
0
Order By: Relevance
“…Not only due to the big advantage of iron as an abundant and economical resource, Fe has attractive features as catalysts and has been employed for the cross‐coupling reaction of oxygen‐containing substrates, including sulfonates, sulfamates,, esters, carbamates, and phosphates . However, the Fe‐catalyzed cross‐coupling reaction of ethers, a simplest unactivated oxygen‐containing family, has not yet been accomplished to date (Scheme b).…”
Section: Methodsmentioning
confidence: 99%
“…Not only due to the big advantage of iron as an abundant and economical resource, Fe has attractive features as catalysts and has been employed for the cross‐coupling reaction of oxygen‐containing substrates, including sulfonates, sulfamates,, esters, carbamates, and phosphates . However, the Fe‐catalyzed cross‐coupling reaction of ethers, a simplest unactivated oxygen‐containing family, has not yet been accomplished to date (Scheme b).…”
Section: Methodsmentioning
confidence: 99%
“…A variety of alkyl and aryl Grignard reagents could be applied and it was demonstrated that the protocol can be readily performed on a gram-scale. In 2016, the group of Frantz reported on a highly stereoselective iron-catalyzed cross coupling using FeCl 3 to couple Grignard reagents and enol carbamates (Scheme 15) [45]. Many functional groups, such as ethers, silanes, primary bromides, alkynes and alkenes, were tolerated.…”
Section: Cross-coupling Reactionsmentioning
confidence: 99%
“… 6 Organic carbamates constitute an important class of compounds, which are widely used in agrochemicals, 7 pharmaceuticals 8 and as intermediates in organic synthesis. 9 Traditional methods for the preparation of carbamates are mainly based on the use of toxic phosgene and its derivatives, which are environmentally unfriendly. 10 In the past decades, many phosgene-free protocols have been explored for the synthesis of carbamates.…”
Section: Introductionmentioning
confidence: 99%